2014
DOI: 10.1186/1475-2891-13-25
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, controlled study of ω-3 fish oil fat emulsion-based parenteral nutrition for patients following surgical resection of gastric tumors

Abstract: BackgroundNutrients such as ω-3 fatty acids including fish oil components eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) suppress the growth and promote apoptosis of tumor cells, improve immune function and reduce the effects of systemic inflammatory response syndrome. We sought to investigate the effect of ω-3 fish oil fat emulsion-based parenteral nutrition (PN) on nutritional state, immune function, inflammatory reaction, expression of tumor factors and complication incidence in patients after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 14 publications
1
58
0
3
Order By: Relevance
“…Minyak ikan diketahui mengandung omega 3 dan omega 6 yang bermanfaat bagi kesehatan jika dikonsumsi sebagai suplemen (Minis et al 2006). Beberapa penelitian menunjukkan bahwa omega 3 dapat menurunkan kadar trigliserida, meningkatkan High Density Lipoprotein (HDL) dan menurunkan kadar Low Density Lipoprotein (LDL) (Covington 2004); mengurangi risiko kerusakan dan penurunan kemampuan kognitif pada lansia (Gonzales et al 2010); meredakan reaksi inflamasi dan mengurangi tingkat komplikasi inflamasi (Wei et al 2014). Cooper (2003) mengatakan bahwa hal ini disebabkan lemak tak jenuh seperti omega 3 diperkirakan memiliki sifat melindungi (protektif) sel saraf dari risiko PA.…”
Section: Pendahuluanunclassified
“…Minyak ikan diketahui mengandung omega 3 dan omega 6 yang bermanfaat bagi kesehatan jika dikonsumsi sebagai suplemen (Minis et al 2006). Beberapa penelitian menunjukkan bahwa omega 3 dapat menurunkan kadar trigliserida, meningkatkan High Density Lipoprotein (HDL) dan menurunkan kadar Low Density Lipoprotein (LDL) (Covington 2004); mengurangi risiko kerusakan dan penurunan kemampuan kognitif pada lansia (Gonzales et al 2010); meredakan reaksi inflamasi dan mengurangi tingkat komplikasi inflamasi (Wei et al 2014). Cooper (2003) mengatakan bahwa hal ini disebabkan lemak tak jenuh seperti omega 3 diperkirakan memiliki sifat melindungi (protektif) sel saraf dari risiko PA.…”
Section: Pendahuluanunclassified
“…Unsaturated fatty acids as precursors of prostaglandins, are important components of cell membranes, which maintain the fluidity of cell membranes, and participate in the regulation of cellular and biochemical responses [7]. Fish oil/kg body weight/day (0.2 g) in addition to TPN has been recommended to be taken by gastrointestinal tumor patients after surgery, for reduction of inflammatory response syndrome and post-operative recovery, on the basis of the fact that ω-3 unsaturated fatty acids inhibit the formation of pro-inflammatory factors (IL-6 and TNF-a), increase the synthesis of antiinflammatory factor IL-10, improve immune function and eliminate excessive inflammation [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the process for identifying potentially eligible studies and exclusion criteria. After elaborative screening, 34 articles were assessed by full text and 17 studies with 753 patients [2,[10][11][12]15,16,[23][24][25][26][27][28][29][30][31][32][33] were included for the review. However, three publications [2,24,30,31,33] are same study that reported different outcomes.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Nine studies reported the occurrence of infectious postoperative complications [11,12,23,26,27,[29][30][31][32]. The incidence of infection was 8.8% in the intervention group (24/273) and 20.1% in the control group (56/271).…”
Section: Clinical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation